Prevalence of depression in Latin America and the Caribbean: protocol for a systematic review and meta-analysis. Issue 1 (13th January 2021) - Errazuriz, Antonia; Crisostomo, Natalia
ABSTRACT: Objective: The objective of this review is to evaluate the best available evidence to determine the prevalence of depression in the general population of Latin America and the Caribbean countries. Introduction: Depression is a common mental disorder that affects quality of life and has been ranked as the largest contributor to non-fatal health loss. Knowledge of this disorder serves as a relevant instrument for policy makers and for the reassignment of public health resources. Although the prevalence of depression is well documented in high-income countries, little is known about the prevalence in Latin America and the Caribbean. Inclusion criteria: This review will include studies that report the prevalence of depression in the general adult (14 years and older) population of countries in Latin America and the Caribbean. Non-representative subsets of the population will be excluded. Methods: The search strategy will be designed to obtain both published and unpublished studies. Information sources include PubMed, PsycINFO, Cochrane CENTRAL, and SciELO. Sources of unpublished studies include literature from government departments, international agencies, and academic institution repositories or websites. Eligible studies will be critically appraised for methodological quality. Prevalence estimates will be statistically pooled in a meta-analysis after heterogeneity interpretation; data not appropriate for pooling will be reported in a narrative review. Finally, risk of publication bias will be studied via funnel plot analysis and the Egger test. Systematic review registration number: PROSPERO (CRD42019143054)